Triboelectric-electromagnetic hybrid nanogenerator driven by wind for self-powered wireless transmission in Internet of Things and self-powered wind speed sensor. (February 2020) - Fan, Xueming; He, Jian; Mu, Jiliang; Qian, Jichao; Zhang, Ning; Yang, Changjun; Hou, Xiaojuan; Geng, Wenping; Wang, Xiangdong; Chou, Xiujian
Abstract: In recent years, as the world has been warming, frequent natural disasters are posing a great threat to humans. By combining 5G technology with the Internet of Things (IoT) concept and increasing the placement of wireless sensor networks, disaster-prone points can be closely monitored. However, regular replacement of the traditional chemical batteries for devices that are a part of the developing IoT remains a significant challenge, especially in remote areas. In this article, we propose and report a hybrid energy harvester used in wind energy harvesting. The device consists of a rotating body and a sliding body. The electromagnetic generators (EMGs) in the rotating body and the triboelectric nanogenerators (TENGs) on the sliding body form the entirety of the power generating mechanism, and all generated units are completely sealed in the device box, which is isolated from the harsh environment. This paper not only systematically studies the influence of dielectric material types and sizes on the output performance of TENGs, but also studies the output performance of this device under different wind speeds. The results show that when the wind speed is not less than 4 m/s, the energy harvester can convert wind energy into electricity. The output performance of TENGs and EMGs increases with increasing wind speed, and the voltages of the TENG and the EMG are 416 V and 63.2 V at the 15 m/s wind speed, respectively. When the wind speed is 9 m/s, the maximum output power of TENG and EMG are 0.36 mW and 18.6 mW, respectively. The device can charge a capacitor of 1000 μF to 19.8 V in 30s. By supplying power to electronic devices and wireless monitoring systems including temperature sensors and humidity sensors, it is shown that the creation and implementation of such an energy harvester is practical and has a significant impact on promoting the development of IoT. Meanwhile, it can be used as a self-powered sensor to detected wind speed by analyzing the frequency of TENG output voltage. Graphical abstract: With the development of 5G technology, energy supply has become an urgent problem to be solved in the popularization of the Internet of things. The device developed in this paper not only has good electrical output performance, but also can be used as a sensor. It has a significant impact on promoting further development toward a functional and revolutionary Internet of Things. Image 1 Highlights: A harvester combined with TENGs and EMGs can harvest energy from wind. It has potential applications prospect in self-powered wireless monitoring system. The device can be used as a self-powered sensor to detect wind speed.